Evaluation of the optic nerve with MRI histogram analysis in Behçet's disease (Annals of Medical Research, 2024)
Aim: The objective of the present study is to analyze whether the optic nerve is affected using histogram analysis on conventional MRI images in patients with Behçet’s disease.Materials and Methods: Gender and age matched patients between the ages of 21 and 75 and a healthy control group were included in the study. Right and left optic nerves of all patients were evaluated by a neuroradiologist using T2-weighted MR images. The optic nerve examination data of the patients were evaluated by histogram analysis. The workstation was a 27 inch iMac computer manufactured by Apple Inc. Cupertino, 88 California, USA.Results: There was no statistically significant difference between the two groups in terms of age and gender (p: 0.927, p: 0.753, respectively). Histogram analysis mean and median values in Behçet's patients were statistically significantly higher than in the healthy control group (p: 0.015, p: 0.006, respectively). The histogram analysis values above the 90th percentile were found to be significantly lower in Behçet's patients with visual symptoms compared to those without visual symptoms.Conclusion: As a result, this study shows that non-macroscopic optic nerve changes can be detected with histogram data analysis of MRI in diseases that can affect the optic nerve such as Behçet's disease. Therefore, we recommend evaluating conventional MR images together with histogram analysis in diseases where optic nerve damage is expected.
Keywords: Behçet’s disease; Histogram analysis; Magnetic rezonans image; Optic nerve